Intergenerational Transmission of Child Abuse Among Married Women in South Korea: A Multigroup Analysis of Empathetic Communication (TSL: Thanks, Sorry, and Love) - Choi, Sunah (Journal of interpersonal violence, 2023)
Intergenerational transmission of child abuse (hereinafter referred to as ITCA) has been continuously reported. Supportive relations with others have also been discussed as a protective factor to prevent this cycle. However, research has mainly investigated supportive adult and peer relationships formed in childhood, with little discussion of the impact of supportive partner relationships formed after becoming an adult. This study examined whether empathetic communication (hereinafter referred to as TSL: “Thanks, Sorry, and Love”) attenuates the transmission of married women’s child abuse experiences to subsequent generations mediated by intimate partner violence (hereinafter referred to as IPV). TSL is a communication strategy that promotes positive communication between intimate partners. We expected TSL to promote positive communication between couples through a process of self-transformation. Data from 1,122 married women were obtained from a nation-wide survey conducted in South Korea. All the survey respondents lived with partners and their own children simultaneously. For this study, structural equation model multigroup analysis was conducted to determine whether the pathways would be attenuated by TSL levels, showing that a high level of TSL communication attenuated the ITCA mediated by IPV. However, this process was maintained in the low-level TSL group. TSL is thus a protective factor against the ITCA. The findings suggest that healing processes can occur not only through childhood relationships but also through those formed after adulthood. Ultimately, to help victims recover, it is necessary to expand communication programs such as TSL that help victims learn how to express their feelings through healthy relationships with their partners.